The European Community and the third world - Erhard Eppler (Intereconomics, 1973)
For quite some time, and with Increasing commitment, people in the member states of the European Community have been discussing the question which role the Community should play in future as regards the developing countries in Africa, Asla and Latin America. From numerous quarters, the view is being voiced with mounting urgency that Europe should contribute more intensively towards solving the manifoid problems of the Third World.
Keywords: 330; Common Market